Extracellular polymer extraction and analysis from UASB granules and batch produced anaerobic granular sludge - Van Eeden, Alida Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc)--Stellenbosch University, 2002.